2008
DOI: 10.1029/2008ja013122
|View full text |Cite
|
Sign up to set email alerts
|

Wave dispersion and the discrete aurora: New constraints derived from high‐speed imagery

Abstract: An analysis of multiscale observations of a substorm auroral breakup are presented which clarify the role of wave dispersion in the formation of elemental (<100 m) auroral structure. At coarse resolution (all‐sky white light camera, 1 frame/s), observations fit the established substorm morphology—namely, arc brightening, formation of spatial distortions, and breakup into multiple “rayed” structures. At fine‐scale resolution (electron multiplying charge‐coupled device [EMCCD] camera, 9‐degree field of view, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 35 publications
7
57
1
Order By: Relevance
“…As pointed out by Semeter et al (2008), already a few degrees off the magnetic zenith can cause a significant error in the width measured from the image. This is especially true for fine-scale aurora.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Semeter et al (2008), already a few degrees off the magnetic zenith can cause a significant error in the width measured from the image. This is especially true for fine-scale aurora.…”
Section: Discussionmentioning
confidence: 99%
“…The range of arc widths (5-35 km) is representitive of a continuous distribution with a lower limit cutoff at 5 km due to the instrument resolution (Partamies et al, 2010). While Knudsen et al (2001) found arc widths larger than 35 km, this result is likely biased towards larger widths due to the aspect angle problem (Semeter et al, 2008;Partamies et al, 2010). Also, Knudsen et al (2001) defined arc widths at 135 km altitude, and so these widths will be slightly larger than those here which are defined at 100 km.…”
Section: Synthetic Imagesmentioning
confidence: 77%
“…The BG3 filter is used to examine only the prompt emissions; it is a notch filter that cuts out the region of the spectrum that contains the slow 557.7 and 630.0 nm emissions and lets in the prompt blue and near-infrared emissions. A transmission curve for the BG3 filter is reproduced in Semeter et al (2008). The high time resolution of the image data reveals flaming aurora, with apparent motion of structures toward the magnetic zenith.…”
Section: Event 1: Substorm Onset With Flaming Aurora -1 March 2011mentioning
confidence: 98%